2015
DOI: 10.1016/j.csbj.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Mediated by P2Y 13 Nucleotide Receptors in Neurons

Abstract: ADP-specific P2Y13 receptor constitutes one of the most recently identified nucleotide receptor and the understanding of their physiological role is currently under investigation. Cerebellar astrocytes and granule neurons provide excellent models to study P2Y13 expression and function since the first identification of ADP-evoked calcium responses not attributable to the related P2Y1 receptor was performed in these cell populations. In this regard, all responses induced by ADP analogues in astrocytes resulted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Another novel finding presented herein is the significant up-regulation of P2Y 13 receptor at Er , indicating that the induction of this P2 purinoceptor may be associated with the resolution of neuroinflammation and a recovery from the disease. The suggestions are corroborated by findings that the activation of P2Y 13 receptor induces main pro-survival pathways in neurons, such as ERK1/2 and PI3K/Akt/GSK3 (Pérez-Sen et al, 2015 ), which are normally activated by trophic factors, and the activation of the Nrf2/HO-1 axis which protects from excitotoxic damage (Espada et al, 2010 ). These findings link ADP to neuroprotection and imply that, in contrast to ATP, ADP may promote survival and increased neuronal resistance to different insults (del Puerto et al, 2012 ).…”
Section: Discussionmentioning
confidence: 78%
“…Another novel finding presented herein is the significant up-regulation of P2Y 13 receptor at Er , indicating that the induction of this P2 purinoceptor may be associated with the resolution of neuroinflammation and a recovery from the disease. The suggestions are corroborated by findings that the activation of P2Y 13 receptor induces main pro-survival pathways in neurons, such as ERK1/2 and PI3K/Akt/GSK3 (Pérez-Sen et al, 2015 ), which are normally activated by trophic factors, and the activation of the Nrf2/HO-1 axis which protects from excitotoxic damage (Espada et al, 2010 ). These findings link ADP to neuroprotection and imply that, in contrast to ATP, ADP may promote survival and increased neuronal resistance to different insults (del Puerto et al, 2012 ).…”
Section: Discussionmentioning
confidence: 78%
“…P2Y 1 , P2Y 2 and P2Y 13 receptors are also present in neurons. P2Y 1 and P2Y 13 receptors together with the ionotrotropic P2X7 receptors regulate neuronal differentiation and are also involved in neuroprotection and neurodegeneration (Miras Portugal et al, 2019; Perez‐Sen et al, 2015). Some P2Y receptors ‐ P2Y 1 , P2Y 2 , and P2Y 4 ‐ appear to be up‐regulated in pathological conditions such as brain injury, Alzheimer's disease, and epilepsy (Franke et al, 2012).…”
Section: P2y Receptors In the Nervous Systemmentioning
confidence: 99%
“…From a recent study on P2Y 2 R knockout (KO) mice and murine cell lines, it was concluded that P2Y 2 R play a neuroprotective role in neurological disorders, especially AD ( de Diego-Garcia et al, 2017 ). Neuroprotection is claimed to be mediated by P2Y 13 nucleotide receptors in neurons ( Pérez-Sen et al, 2015 ). Activation of P2Y 2 R evokes regeneration of glial cells and nerves and the P2YR-like GPR17 evokes oligodendrocyte regeneration.…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%